Endoscopic decompression of acute intestinal distension is associated with reduced mortality in critically ill patients - Book, Thorsten (BMC Gastroenterol, 2020)
BACKGROUND: Endoscopic placement of intestinal decompression tubes is a feasible technique for treatment of acute intestinal dilation. Given the heterogeneity of the underlying diseases leading to intestinal obstruction data on the significance of endoscopic procedures for treatment of these conditions are sparse. METHODS: In the study period from 2008 to 2019 all patients receiving a decompression tube were identified by retrospective chart review and analyzed. RESULTS: A total of 59 decompression tubes were placed in 50 patients. Technical success was achieved in 98% (58/59 tubes). As major complication one small bowel perforation occurred (1/59; 1.7%). Causes for impaired intestinal transit comprised tumor stenoses 22% (11/50), infections 18% (9/50), post-operative paralysis 14% (7/50), neurological diseases 8% (4/50), trauma 2% (1/50) and others 36% (18/50). Most patients (74%; 37/50) were critically ill and treated on intensive care unit. Treatment response after tube insertion was documented in 76% of patients (38/50) whereas 24% (12/50) did not fulfill response criteria. Patients with treatment response showed a significantly better outcome compared to non-responders. Responders had a median survival of 113 days (95% CI 41–186) compared to 15 days (95% CI 6–24) in non-responders (p = 0.002). Analysis of laboratory parameters after stratification in responders and non-responders to endoscopic therapy showed that non-responders had significantly higher levels of CRP and lower platelet count at baseline (CRP 262 mg/L (IQR 101–307) vs. 94 mg/L (IQR 26–153): p = 0.027; platelets 69 thsd/μL (IQR 33–161) vs. 199 thsd/μL (IQR 138–289): p = 0.009). CONCLUSIONS: Endoscopic decompression is a safe procedure for acute management of impaired intestinal transit even in critically ill patients. Response to therapy is associated with improved outcome and markers of inflammation and organ function such as CRP, platelet count and serum lactate have to be taken into account for therapy monitoring and evaluation of prognosis.